Pulmonary Actinomycosis attributable to Actinomyces meyeri presenting as cardiac tamponade: a case report - Nishizawa, Saori; Anan, Keisuke; Tobino, Kazunori; Okahisa, Masanobu; Goto, Yuki; Murakami, Kojin; Sueyasu, Takuto; Munechika, Miyuki; Yoshimine, Kohei; Yoshino, Mai (Multidisciplinary Respiratory Medicine, 2018)
Background: Recently, it is reported that Actinomyces meyeri is the most common species causing actinomycosis. However, to our knowledge, there was no report about pulmonary actinomycosis attributable to A. meyeri presenting as cardiac tamponade. Case presentation: Hereby we describe a case of pulmonary actinomycosis attributable to A. meyeri presenting as cardiac tamponade. At first, the patient was diagnosed with bacterial pericarditis with lung abscess in the left lower lung lobe and underwent pericardial drainage. Three days after the removal of the drainage tube, atrial fibrillation followed by cardiac arrest with asystole occurred and immediate cardiopulmonary resuscitation restored his circulation. Thereafter, he underwent pneumocentesis of the lung abscess and the culture grew A. meyeri. He was successfully treated with penicillin G. Conclusion: This is the first case of pulmonary actinomycosis attributable to A. meyeri presenting as cardiac tamponade. We believe that an increased awareness of the disease is necessary to expedite diagnosis therefore minimizing morbidity and mortality.